(untitled) (De la Crítica, 2023)
This article deals with an investigation carried out in the educational context of the Experimental Center for Comprehensive Care of Boys and Girls of the Francisco de Miranda University, Falcón state choir in the period 2018-2020, where teachers and students of primary education participated. ; who were the key informants of said investigation. The main purpose of it was focused on implementing an Environmental Literacy Program: A Critical Approach in Primary Education: where the techniques and instruments used to gather information were: Participant observation, conversations, work tables, field diary, records, recordings, interviews and estimation scale. It should be noted; that the research was based on Brunner’s discovery learning theory under the postulates of Paulo Freire and Adorno: it was developed under the Sociocritical paradigm with the IAP participant action research method; in order to transform reality through a set of actions from the pedagogical praxis of teachers in environmental matters in the early stages or levels of education. The results obtained in the investigative process and implementation of the environmental literacy program for teachers and students at the aforementioned level allowed them to empower themselves and generate an environmental pedagogical praxis that led the student to reflect, act and create an environmental awareness where he could generate the changes contributing to have a different vision of how to approach environmental education with a critical sense and co-responsibility from their educational field and in terms of teachers innovated their strategies regarding how to approach environmental education in an integrated way to form a critical student